Nocturnal Melolonthidae (Coleoptera) collected in agave fields of Jalisco, Mexico - Lugo-García, Gabriel Antonio; Ortega-Arenas, Laura Delia; González-Hernández, Héctor; Aragón-García, Agustín; Romero-Nápoles, Jesús; Rubio-Cortés, Ramón; Morón, Miguel Ángel (Instituto de Ecología, A.C., 2011)
In order to know the nocturnal fauna of Melolonthidae from the main agave tequilero fields in Jalisco, Mexico, monthly captures of adults were carried out from May to August 2007, using a fluorescent light black trap, funnel type, in Ixtlahuacán del Río, Tepatitlán de Morelos and San Juanito de Escobedo, Jalisco, Mexico. A total of 57,263 specimens included in 20 species were collected. Phyllophaga ravida (Blanchard) (58.7%), Paranomala cincta (Say) (14.1%), hyllophaga misteca (Bates) (11.6), P. dentex (Bates) (2.5%) and Paranomala hoepfneri (Bates) (1.8%) were the best represented species. The highest abundance was registered in June (96%) and the lowest capture in July. The greatest species richness (17 species) was recorded in Tepatitlán de Morelos. A key to identify the recorded species is included.